The Impact of Gut Microbiota on Gender-Specific Differences in Immunity - Fransen, Floris; van Beek, Adriaan A.; Borghuis, Theo; Meijer, Ben; Hugenholtz, Floor; van der Gaast-de Jongh, Christa; Savelkoul, Huub F.; de Jonge, Marien I.; Faas, Marijke M.; Boekschoten, Mark V.; Smidt, Hauke; El Aidy, Sahar; et al. (Frontiers in Immunology, 2017)
Males and females are known to have gender-specific differences in their immune system and gut microbiota composition. Whether these differences in gut microbiota composition are a cause or consequence of differences in the immune system is not known. To investigate this issue, gut microbiota from conventional males or females was transferred to germ-free animals of the same or opposing gender. We demonstrate that microbiota-independent gender differences in immunity are already present in germ-free mice. In particular type I interferon signaling was enhanced in the intestine of germ-free females. Presumably, due to these immune differences bacterial groups such as Alistipes, Rikenella, and Porphyromonadaceae known to expand in the absence of innate immune defense mechanism were overrepresented in the male microbiota. The presence of these bacterial groups was associated with induction of weight loss, inflammation, and DNA damage upon transfer of the male microbiota to female germ-free recipients. In summary, our data suggests that microbiota-independent gender differences in the immune system select a gender-specific gut microbiota composition, which in turn further contributes to gender differences in the immune system.